Benign convulsion with mild gastroenteritis - Ben Kang; Young Se Kwon (Korean Pediatric Society, 2014)
Benign convulsion with mild gastroenteritis (CwG) is a type of afebrile seizure that occurs in children. CwG is defined as a convulsion in a previously healthy child with no known central nervous system infection or encephalopathy, accompanying mild diarrhea without fever, electrolyte imbalance, or moderate to severe dehydration. Convulsions in CwG are characterized by multiple brief episodes of generalized or focal seizures. Although the etiology and pathophysiology have yet to be fully explained, many pathogenic mechanisms have been proposed including the possibility of direct invasion of the central nervous system by a gastrointestinal virus such as rotavirus or the possibility of indirect influence by the production and effects of certain mediators. The electroencephalogram findings are benign and long-term antiepileptic treatment is typically not required. Long-term prognosis has been favorable with normal psychomotor development. This review provides a general overview of CwG with the goal of allowing physicians practicing in the field of pediatrics to better recognize this unique entity and, ultimately, to minimize unnecessary evaluation and treatment.